2012
DOI: 10.5194/acp-12-12081-2012
|View full text |Cite
|
Sign up to set email alerts
|

On the origin of subvisible cirrus clouds in the tropical upper troposphere

Abstract: Abstract. Spaceborne lidar observations have recently revealed a previously undetected significant population of Subvisible Cirrus (SVC). We show them to be colder than −74 • , with an optical depth below 0.0015 on average. The formation and persistence over time of this new cloud population could be related to several atmospheric phenomena. In this paper, we investigate if these clouds follow the same formation mechanisms as the general tropical cirrus population (including convection and in-situ ice nucleati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 80 publications
3
18
0
1
Order By: Relevance
“…Overall, these results suggest that, at the instantaneous scale of cloud measurements, the water vapour response along the whole troposphere in correspondence to ice cloud profiles is well predicted only accounting for their capability to backscatter radiation (given by the observed SR profile). While the large-scale link between relative humidity and the cloud properties (vertical distribution, phase, and opacity) has been well documented in previous studies (Martins et al, 2011;Reverdy et al, 2012), this work represents the evidence that this relationship can also be detected at much smaller spatio-temporal scales. The emergence of a clear signal at these fine scales also highlights the limitations of SAPHIR measurements: although SAPHIR observes the water vapour field at a much finer horizontal resolution than what is currently available in reanalysis products, in order to explain physical processes, downscaled observations are needed.…”
Section: Resultssupporting
confidence: 63%
“…Overall, these results suggest that, at the instantaneous scale of cloud measurements, the water vapour response along the whole troposphere in correspondence to ice cloud profiles is well predicted only accounting for their capability to backscatter radiation (given by the observed SR profile). While the large-scale link between relative humidity and the cloud properties (vertical distribution, phase, and opacity) has been well documented in previous studies (Martins et al, 2011;Reverdy et al, 2012), this work represents the evidence that this relationship can also be detected at much smaller spatio-temporal scales. The emergence of a clear signal at these fine scales also highlights the limitations of SAPHIR measurements: although SAPHIR observes the water vapour field at a much finer horizontal resolution than what is currently available in reanalysis products, in order to explain physical processes, downscaled observations are needed.…”
Section: Resultssupporting
confidence: 63%
“…The cloud optical depth (τ) is not provided in the data set we used, so we calculate the optical depth of single-layer cirrus clouds using the formulation of Reverdy et al [2012]:…”
Section: Methodsmentioning
confidence: 99%
“…Such processes include cirrus cloud formation, dehydration, and transport of gaseous chemical species and aerosols to the stratosphere. Because they strongly depend on the history of air parcels, i.e., on the Lagrangian evolution of temperature, humidity, and diabatic heating, these processes are often investigated using trajectories calculated with (re)analysis products [e.g., Fueglistaler et al , ; Reverdy et al , ; Liu et al , ]. In these studies, errors in the analyzed wind fields have been identified as a potential source of uncertainty in the results, and, for instance, Hasebe et al [] reported on differences that can reach a few m/s between analyzed and observed winds in the TTL over the Maritime Continent.…”
Section: Introductionmentioning
confidence: 99%